Duplex kidney anomalies and associated pathology: a single centre retrospective review - Sarma, Debanga; Pratihar, Sarbartha Kumar; T. P., Rajeev; Barua, Sasanka K.; Bagchi, Puskal K.; Phukan, Mandeep (International Surgery Journal, 2019)
Background: Duplex kidneys are common developmental renal anomaly with an incidence of 1% in healthy adult population.Adult individuals may present as non-functional moiety, calculus disease or an incidental finding. Duplex kidney is defined as a renal unit comprised of two pelvicalyceal systems. Based on the degree of fusion, it can present as bifid renal pelvis, partial ureteric duplication (Y-shaped ureter), incomplete ureteric duplication with ureters joining near or in bladder wall (V-shaped ureter) and complete ureteric duplication with separate ureteric orifices. The purpose of this study is to retrospectively review the various duplex kidney anomalies and associated pathology. Methods: This is a retrospective study, performed at Department of Urology, Gauhati Medical College Hospital, a tertiary centre, from September, 2018 to August, 2019. Preoperative imaging, plain intravenous urography or computed tomography intravenous urography was done. Results: 29 patients were diagnosed with variants of duplex kidney anomaly. It includes right side, left side and bilateral anomalies. Among all the patients 4 had incidental findings. 16 patients had associated renal or ureteral calculus. 5 patients had associated ureteropelvic junction obstruction while 1 patient had ureterovesical junction stricture. We found single patient in each group of duplex kidney anomaly associated with non-functional moiety with renal cell carcinoma, ureterocele with urothelial malignancy and horseshoe kidney with ureteropelvic junction obstruction respectively. Conclusions: Duplex kidney anomaly in most individuals is of no clinical significance. High index of suspicion along with good quality imaging can accurately detect specific anomaly and associated condition.